Study on the factor that affecting the employee retention at Anfi Industries Sdn. Bhd / Nurul Aina Salleh - Salleh, Nurul Aina (Faculty of Business and Management, 2018)
The purpose of this study is to identify the relationship between three chosen factors; supportive working environment, pay, and training and development towards employee retention among employees at Anfi Industries Sdn. Bhd. The overall population in Anfi Industries is 170. This study is used sample of 91. The instrument used is a questionnaire consisting of five sections and 35 items. The returned rate of the questionnaire is only 88. Researcher used the Statistical Packages for Social Science (SPSS) version 20. The sampling technique that has been used by the researcher is simple random sampling. The data was analyzed using Reliability Test, Descriptive Analysis, Pearson’s Correlation Analysis and Multiple Regression Analysis. Result from Reliability Test showed very good strength of association of each variable. Analysis of this survey showed only two independent variables have a significant relationship with employee retention. Another one variables does not have any significant relationship with employee retention. The findings of this study also indicated that the most influence factor among the three independent variables tested that affected employee retention is supportive working environment.